The Owners of Xenophobia: Zimbabwean Informal Enterprise and Xenophobic Violence in South Africa - Crush, Jonathan; Tawodzera, Godfrey; Chikanda, Abel; Tevera, Daniel (African Human Mobility Review, 2021)
This paper is a contribution to our understanding of the intertwined economicand political crises in Zimbabwe and the crisis of xenophobia in South Africa.There have been few studies to date specifically examining the impact ofxenophobic violence on Zimbabweans trying to make a living in the SouthAfrican informal economy. The paper first provides a picture of Zimbabweanmigrant entrepreneurship using survey data from a 2015 study of migrants inthe informal economy. All of the Zimbabwean entrepreneurs interviewed indepth for the study in 2016 had either witnessed or been the victims ofxenophobic violence or both. The interviews focused on the experience andimpact of xenophobic violence on personal safety and business operations. Themigrant accounts clearly demonstrate that they see xenophobia as a key driverof the hostility, looting and violence that they experience. The paper argues thatthe deep-rooted crisis in Zimbabwe, which has driven many to South Africa in thefirst place, makes return home in the face of xenophobia a non-viable option.Zimbabweans are forced to adopt a number of self-protection strategies, none ofwhich ultimately provide insurance against future attack.